The Sufficiency Economy Philosophy and Small and Medium-sized Enterprises in Thailand - Suntrayuth, Sid (International Review of Management and Marketing, 2018)
Business owners are facing with many challenges in an ever changing and more complex business environment. In today competitive business environment is characterized by change and innovation. Moreover, small and medium-sized enterprises (SMEs) play a significant role in the Thai economy. This research aims to investigate conditions in which Sufficiency Economy Philosophy (SEP) will become significant when apply to SMEs business operations. The qualitative methodology was utilized in order to answer the research question. It was found that many SMEs applied SEP as a risk management procedure where there is a high intensity of competition and during rather stable to low economic growth. Moreover, the level of changes in social condition and political tension can also cause the likelihood for many SMEs to apply SEP in the business operation. Keywords: sufficiency economy philosophy (SEP), small and medium-sized enterprises (SMEs), border SMEs, application of SEP JEL Classification: M0